Application for Reporting Damage to Roads & Bridges at UPT DBMSDA Tangerang Regency - Desy Apriani; Syafira Viglia Zumadilla; Ginanjar Putro Wicaksono (Universitas Raharja, 2023)
The development of special science and technology of the internet has developed very rapidly and provides very significant developments in our daily lives. In addition, the presence of technology in the company's environment is also familiar. Overcoming the Internet in various fields. The more rapid technology drives the company or more optimal in its performance. This discusses the Tangerang District Water and Water Resources Office as an institution engaged in the service and community sectors to improve the road and bridge reporting system to create more effective and efficient performance. The UPT of Binamarga Service and Water Resources of Tangerang Regency still has various problems, the difficulty in reporting road damage is less fast and less accurate the process is still manual. This research uses the SWOT method, system requirements determination and system modeling using UML (Unified Modeling Language) to describe the visualization, and then uses the MySQL-Server database as the database to implement the hypertext preprocessor (PHP) programming language. Therefore, it is necessary to improve the system to use the Tangerang District Water and Water Resources Service in reporting damage to roads and bridges so that the Tangerang District Water Service and Water Resources Department can immediately display and process the approved reports to assist the DGH sector.